Media and new religions in Japan (2016)
One night, during one of my first visits to Tokyo, I was waiting for the green light at the Shibuya pedestrian crossing. One of the busiest intersections in the world, it is surrounded by advertising signs and large video screens mounted on buildings overlooking the crossing, often showing the latest pop stars’ music videos or advertising. One of these screens was showing rapidly moving images of young people playing different sports. I assumed this was the new advertisement of some well-known sport clothes brand, but at the end of the short video, the message “Possibilities are endless, Sōka Gakkai” (kanōsei wa mugendai, Sōka Gakkai) appeared on the screen. Sōka Gakkai is the largest new Buddhist organisation in Japan and advertisements of its publications frequently appear in newspapers and on television1 and trains. However, Sōka Gakkai’s engagement with media and advertising is not unique among Japanese (new) religious organisations. In fact, it is just one example of the ways in which such movements seek to attract attention and get their messages across by using mass media strategies and advertising activities. For example, in July 1991, several thousand people gathered in the Tokyo Dome, a large baseball stadium in central Tokyo, to attend the “transformation” of Ōkawa Ryūhō, the leader of a religious movement called Kōfuku no Kagaku (literally, Science of Happiness, but now officially calling itself Happy Science in English), who proclaimed his true identity as a supreme deity called El Cantāre during a spectacular event and performance. In the months before the event, the group coordinated an intensive and expensive advertising campaign that prophesied the arrival of a new era with the slogan, “Now is the Age of Kōfuku no Kagaku” (Jidai wa ima, Kōfuku no Kagaku). Around the same period, Asahara Shōkō, the leader of Aum Shinrikyō, the group that later became notorious for committing the sarin gas attack on the Tokyo subway in 1995 and other atrocious crimes, was invited as a guest on TV talk shows, and his group, although sharply critical of modern society and media, was one of the first groups in Japan to engage with computer-based communication